Meat quality from fighting bulls in Spain - Beriain, María José; Horcada, Alberto; Lizaso, Guadalupe; Insausti, Kizkitza; Purroy, Antonio (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Spaniard beef derived from “running bulls” are consumed during the festival days as has become traditional at every annual San Fermin fair. However, eating quality, safety and chemical composition of beef derived from these animals are generally unknown. The present work characterized beef from San FerminÂ´s fighting bulls (SFRB) by conducting microbiological test analyses of selected physical-chemical traits including fatty acid composition of intramuscular lipids during ageing. Beef from fighting bulls was characterized by a dark red colour, due to its high pH values (pH48hours= 6.2). However, this beef did not show any dry firm dark (DFD) characteristic, as usually occurs with meat from other beef breeds with final pH higher than 6.0. The high myoglobine content (10.6 mg”¢g-1) and the low intramuscular fat percentage (1.5%) provide this beef with adequate nutritional properties for the diet/health consumer. The fatty acids (FA) profile stands out because of its high nutritional interest, due to the fact that polyunsaturated FA were higher than 20% of total FA in the muscle. The obtained results allow the differentiation of this kind of beef and it will contribute to setting up a quality mark or label because consumer evaluates positively those meat products that come from animals reared in extensive livestock systems.